2019
DOI: 10.1002/adma.201807406
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Composition, Electronic Structure, Disorder, and Doping due to Dual Sublattice Mixing in Nonequilibrium Synthesis of ZnSnN2:O

Abstract: The opportunity for enhanced functional properties in semiconductor solid solutions has attracted vast scientific interest for a variety of novel applications. However, the functional versatility originating from the additional degrees of freedom due to atomic composition and ordering comes along with new challenges in characterization and modeling. Developing predictive synthesisstructure-property relationships is prerequisite for effective materials design strategies. Here, we present a first-principles base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 65 publications
1
42
1
Order By: Relevance
“…We theoretically explained that the carrier density in ZnSnN2 decreases to 10 17 cm -3 with increasing Zn and O content due to formation of defect complexes and modification of the material electronic structure. 13 Further, we experimentally showed that annealing Zn1+xSn1-xN2 grown with added hydrogen reduces its free electron density by orders of magnitude, down to 4 × 10 16 cm -3 . 14 These carrier densities are low enough for formation of rectifying heterojunctions necessary for solar cell fabrication, according to modeling.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We theoretically explained that the carrier density in ZnSnN2 decreases to 10 17 cm -3 with increasing Zn and O content due to formation of defect complexes and modification of the material electronic structure. 13 Further, we experimentally showed that annealing Zn1+xSn1-xN2 grown with added hydrogen reduces its free electron density by orders of magnitude, down to 4 × 10 16 cm -3 . 14 These carrier densities are low enough for formation of rectifying heterojunctions necessary for solar cell fabrication, according to modeling.…”
Section: Discussionmentioning
confidence: 88%
“…To explain the unusual ZTN material properties, we developed an approach to go beyond the conventional defect model by considering the additional effects of non-equilibrium synthesis, off-stoichiometry, disorder, and (intentional or unintentional) incorporation of impurities, thereby capturing the physics of non-ideal complex mixed-ion semiconductor materials. 13 The ZTN calculations results ( Fig.1) show that the net doping is a non-monotononic function of the Zn and O content, which has been considered as anomalous/unusual in the past. The non-monotonic behavior is mainly due to the composition induced changes in the electronic structure, namely change in the band position and the resulting change in defect formation enthalpies at high Zn and O content.…”
Section: Project Results and Discussionmentioning
confidence: 97%
“…Defect equilibrium, by accounting for both defect and defect pair binding, was obtained by solving the self-consistent equation by forcing the charge neutrality between free carriers and charged defects. 10,24,25 Since the carrier concentration depends on the relative distance of Fermi level to the band edges, oxygen induced band edge shifts were also included in the defect equilibrium simulation. 10 At T ¼ 700 K, the defect equilibrium calculation was conducted as a function of oxygen content under Zn-rich conditions (Zn 3 N 2 limit).…”
Section: Methodsmentioning
confidence: 99%
“…10,24,25 Since the carrier concentration depends on the relative distance of Fermi level to the band edges, oxygen induced band edge shifts were also included in the defect equilibrium simulation. 10 At T ¼ 700 K, the defect equilibrium calculation was conducted as a function of oxygen content under Zn-rich conditions (Zn 3 N 2 limit). Two defect pairs, (Zn Sn ÀO N ) À and (Zn Sn À2O N ) 0 , play important roles with the pair binding energies about À0:97 eV and À1:73 eV, respectively, relative to the isolated Zn 2À Sn and O þ N defects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation